1994
DOI: 10.1007/bf00762735
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on regulation of the mitochondrial permeability transition pore; a cyclosporin-sensitive pore in the inner mitochondrial membrane

Abstract: The mitochondrial permeability transition pore allows solutes with a m.w. approximately less than 1500 to equilibrate across the inner membrane. A closed pore is favored by cyclosporin A acting at a high-affinity site, which may be the matrix space cylophilin isozyme. Early results obtained with cyclosporin A analogs and metabolites support this hypothesis. Inhibition by cyclosporin does not appear to require inhibition of calcineurin activity; however, it may relate to inhibition of cyclophilin peptide bond i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
342
1
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(355 citation statements)
references
References 54 publications
10
342
1
2
Order By: Relevance
“…The MPT induction is strongly regulated by both Dc and DpH components of the mitochondrial protonmotive force, divalent cations and different metabolites [38], in addition to the thiol redox status of cysteine residues in the vicinity of the voltage sensor of the pore that determines the probability of MPT induction [18,19,30]. Moreover, the MPT possesses at least two redox-sensitive sites, one of them in equilibrium with GSH of mitochondrial matrix and another that can be directly activated by ROS [30].…”
Section: Discussionmentioning
confidence: 99%
“…The MPT induction is strongly regulated by both Dc and DpH components of the mitochondrial protonmotive force, divalent cations and different metabolites [38], in addition to the thiol redox status of cysteine residues in the vicinity of the voltage sensor of the pore that determines the probability of MPT induction [18,19,30]. Moreover, the MPT possesses at least two redox-sensitive sites, one of them in equilibrium with GSH of mitochondrial matrix and another that can be directly activated by ROS [30].…”
Section: Discussionmentioning
confidence: 99%
“…CsA is a high-affinity inhibitor of a pore in the matrixdelimiting mitochondrial membrane [15,34]. Pore opening or permanence of the pore in an open state is favored by Ca 2+ or depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that pro-apoptotic Bcl-2 family members (Bax, Bak, Bid, and Bik) induce apoptotic changes in isolated mitochondria that are prevented by Bcl-2 and Bcl-x L (JuÈ rgensmeier et al, 1998;Narita et al, 1998;Eskes et al, 1998;Shimizu and Tsujimoto, 2000). Although there seems to be controversy, it has been shown that Bax-and Bak-induced mitochondrial changes are mediated by a polyprotein channel called the permeability transition (PT) pore (Narita et al, 1998;Marzo et al, 1998), which is considered to form at sites of contact between the mitochondrial inner and outer membranes and to consist of mitochondrial porin (also called the voltage-dependent anion channel, VDAC), the adenine nucleotide translocator (ANT), cyclophilin D, and some other molecules (reviewed by Bernardi et al, 1994;Zoratti and Szabo , 1995). VDAC is an abundant outer mitochondrial membrane protein that forms a large (53 nm) voltage-gated pore when incorporated into planar lipid bilayers (reviewed by Colombini, 1989).…”
Section: Introductionmentioning
confidence: 99%